Employee Performance Analysis Based on the Effect of Discipline, Motivation, and Organizational Commitment at the Regional Secretariat of the Kupang City Government - Jefirstson Richset Riwukore; Luis Marnisah; Fellyanus Habaora (Jurnal Maksipreneur, 2022)
The purpose of this research is to analyze and prove the influence of discipline, motivation, and organizational commitment on employee performance. For three months the research was carried out, starting from January to March 2022 at the Regional Secretariat of the Kupang City Government. This research belongs to the type of quantitative research using primary data collected through filling out questionnaires (closed questions using a Likert scale) for 60 days of data collection. The population in this study was 1034 employees. The number of research samples was 288 respondents which were determined by proportional stratified random sampling and the Slovin technique. Data analysis used multiple linear regression analysis using SPSS version 25 application tools. The results showed that there was a strong and significant influence between discipline, motivation, and organizational commitment variables on employee performance at the Regional Secretariat of the Kupang City Government.